The Video Media Development for Teaching Local History Course: Title “History of The City of Samburi” Social, Religion, and Culture Study Learning Group for Elementary Students Grade 4 at Phibun Songkhro 1 School - Petchvichit, Phanthip; Inthanee, Nunthawas; Wareenil, Thanaporn; Panichayapan, Panadda (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The objectives of this present study were 1) to develop the video media related to local history entitled “Samburi Historical Community Development” to achieve the 80/80 efficiency criteria; 2) to compare study achievement before and after using local history video media; 3) to evaluate satisfaction of student using local history video media in classes. The target group in this research was 33 fourth graders at Phibun Songkhro 1 School in the second semester of the academic year 2021. The research tools used in this study were the video media related to local history entitled “Samburi Historical Community Development”, lesson plan, study achievement measurement form, and satisfaction measurement form. The statistics used in the data analysis were the efficiency (E1/E2), means, and standard deviation. The research findings revealed that 1. the video media related to local history entitled “Samburi Historical Community Development elicited a quality assessment score at the highest level with the efficiency (E1/E2) of 86.53/82.50 in accordance with the 80/80 efficiency criteria; 2. the students achievement of the fourth graders revealed that their posttest score were higher than that of the pretest. The score differed at +4.39; 3. students were satisfied with implementing the video media related to local history entitled “Samburi Historical Community Development. Its overall satisfaction in all 4 aspects was at the highest level.